STRATEGI PEDAGANG PASAR GROSIR CIPULIR DENGAN PERKEMBANGAN TEKNOLOGI 2010-2022 - Naquein, Sulthon; Asri, Zul (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
The Cipulir Market is a wholesale market with good potential, the potential has been enhanced with the development of the times, which in its development, presents additional trading strategies in Cipulir Market. The purpose of this research is to look at changes in trading strategies carried out by Cipulir Market traders considering technological developments. The method used is the historical method with heuristics, verification, interpretation, and historiography. The results of the study found a correlation between the development of the technological era and the strategy of Cipulir Market traders. This can be seen from the development of banking technology, social media, and online stores, where in some periods there have been significant changes. For instance, what used to be payments that could only be made in cash can now be made using mobile banking applications; the use of social media, which was previously only used to establish communication, is now used by traders to promote directly to consumers; and the use of online stores, which were previously doubted by traders, is now convinced by the existence of offline stores that can be visited directly if there is a mismatch in the products offered. These are the evidence of technological developments that support and add to the trading strategies carried out by Cipulir Market traders.